PTH-031 The outcomes of ERCP for common bile duct gallstones in england between 2003 and 2015. (8th June 2018) - Harvey, Philip; Baldwin, Simon; Mytton, Jemma; Coupland, Ben; Evison, Felicity; Patel, Prashant; Trudgill, Nigel
Abstract : Introduction: The BSG ERCP standards suggest duct clearance should be achieved in >85% of ERCPs for common bile duct gallstones. However recent data on ERCP for palliation of malignant biliary obstruction demonstrated significant variation in outcomes between providers related to procedure volume. We have therefore examined outcomes of ERCPs for common bile duct gallstones. Methods: Hospital Episode Statistics (HES) include diagnostic and procedural data for all hospital attendances in England. All subjects undergoing their first ERCP, with the ICD10 code K80 (cholelithiasis) were included. Subjects with a relevant cancer diagnosis 2 years before, or after ERCP were excluded. Associations between demographics, co-morbidities and unit ERCP volume were examined by logistic regression analysis. Not needing to undergo repeat ERCP within 90 days was considered a surrogate for successful duct clearance. Results: 98 887 subjects were included, 65.5% were female, their median age was 68(IQR 52–79) and 72.3%, 13.8% and 13.9% had a Charlson co-morbidity score of 0, 1–4 and >4 respectively. Approximately half were elective procedures(50.8%). 86.6% did not require repeat ERCP within 90 days; 12.1% required 1 repeat; and 1.3% required 2 or more repeats. The following factors were associated with not needing a repeat ERCP; Charlson co-morbidity score >4 (OR 0.83 (95% CI:0.78–0.88), p<0.001), age >81 (0.82(0.77–0.88), p<0.001), and outpatient procedures (0.80 (0.76–0.84), p<0.001). Provider volume, (volume knot 1 (1.00(1.00–1.00), p=0.135), knot 2 (1.00(1.00–1.00), p=0.523), knot 3 (1.00(1.00–1.01), p=0.333)), year of procedure and emergency admission type were not associated with needing a repeat ERCP within 90 days. Needing a repeat ERCP was associated with; Asian ethnicity (1.18 (1.06–1.31), p=0.002), Black ethnicity (1.22 (1.03–1.45), p=0.023), mixed ethnicity (1.51 (1.14–2.01), p=0.005), age quintile 47–62 (1.10(1.04–1.17), p=0.001), age 63–72 (1.09(1.03–1.16), p=0.004) and male gender (1.12 (1.02–1.45), p<0.001). Conclusions: The BSG key performance indicator for stone clearance at first ERCP (>85%) appears to be achieved overall, assuming that no repeat ERCP within 3 months is a marker of successful stone clearance. Not needing a repeat ERCP for common bile duct stones was associated with outpatient procedures, very old and co-morbid subjects. Increased ERCP volume and year of ERCP (2003–2015) did not change the apparent of success rate of stone clearance at ERCP.